2021
DOI: 10.3390/ijerph18105308
|View full text |Cite
|
Sign up to set email alerts
|

Burnout in Professional Psychotherapists: Relationships with Self-Compassion, Work–Life Balance, and Telepressure

Abstract: Though negative impacts of COVID-19 on occupational mental health have been reported, the mental health of psychotherapists has not been evaluated in depth. As this occupational group treats ever-increasing mental health problems, it is essential to appraise key factors for their mental health. Accordingly, this study aimed to explore burnout of professional psychotherapists. A total of 110 participants completed self-report measures regarding burnout, self-compassion, work–life balance and telepressure. Corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 64 publications
2
28
0
4
Order By: Relevance
“… 43 Master’s counselling interns 152 SOFI; FFMQ Mindfulness (+); Compassion for others (+) Mindfulness → Self-compassion → Compassion for others Kotera et al (2021). 28 Psychotherapists 126 MBI (2-items); SCS-SF; WLBC; TS Emotional exhaustion (-); depersonalisation (-); work-life balance (+) Work-life balance → Self-compassion → Emotional exhaustion Latorre et al (2021). 41 Counselling and clinical psychology doctoral trainees 192 SCS-SF; MAAS; CSES; PCS-R Mindfulness (+); self-efficacy (+); professional competencies (+) Mindfulness → Self-compassion → Self-efficacy Mindfulness → Self-compassion → Self-assessed professional competency McCade et al (2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 43 Master’s counselling interns 152 SOFI; FFMQ Mindfulness (+); Compassion for others (+) Mindfulness → Self-compassion → Compassion for others Kotera et al (2021). 28 Psychotherapists 126 MBI (2-items); SCS-SF; WLBC; TS Emotional exhaustion (-); depersonalisation (-); work-life balance (+) Work-life balance → Self-compassion → Emotional exhaustion Latorre et al (2021). 41 Counselling and clinical psychology doctoral trainees 192 SCS-SF; MAAS; CSES; PCS-R Mindfulness (+); self-efficacy (+); professional competencies (+) Mindfulness → Self-compassion → Self-efficacy Mindfulness → Self-compassion → Self-assessed professional competency McCade et al (2021).…”
Section: Resultsmentioning
confidence: 99%
“… 29 In addition, self-compassion appeared linked to a better balance between professional and personal life, with self-compassion mediating the relationship between work-life balance and emotional exhaustion. 28 From a qualitative perspective, Patsiopoulos and Buchanan 45 have also mentioned, among the benefits of self-compassion, better management of occupational stress and challenges involved at therapeutic work. Here, compassion is a factor contributing to quality of working life.…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to sociodemographic correlates of burnout among psychotherapists, it appears that, in particular, age and gender play a significant role. Firstly, a total of nine relevant studies (i.e., those which provided data on the age-burnout association) revealed that younger psychotherapists tend to report increased levels of burnout symptoms in comparison to older and more experienced colleagues in that profession (Ackerley et al, 1988 ; Huberty and Huebner, 1988 ; van der Ploeg et al, 1990 ; Rupert and Kent, 2007 ; Rasmussen et al, 2016 ; Berjot et al, 2017 ; Allwood et al, 2020 ; Tsai et al, 2020 ; Kotera et al, 2021 ). This finding is consistent with the previous meta-analysis concerning the aforementioned relationship in various employment settings (Brewer and Shapard, 2004 ).…”
Section: Summary Of Findings and Main Conclusionmentioning
confidence: 99%
“…Finally, concerning work-related covariates, workload, and/or work experience, work settings and supervision/personal therapy exerted relatively homogenous effects on burnout. Six studies have revealed significant associations between high workload and increased levels of burnout (Huberty and Huebner, 1988 ; Raquepaw and Miller, 1989 ; Rupert and Kent, 2007 ; Rupert et al, 2009 ; Kim, 2017 ; Kotera et al, 2021 ). Similarly, four studies have suggested that less experienced psychotherapists were particularly vulnerable to burnout compared to their more experienced colleagues (van der Ploeg et al, 1990 ; Mills and Huebner, 1998 ; di Benedetto and Swadling, 2014 ; Kim, 2017 ).…”
Section: Summary Of Findings and Main Conclusionmentioning
confidence: 99%
“…The literature has shown positive associations between self-compassion and favorable mental health outcomes [27,[29][30][31]. Notably, studies carried out in the context of the COVID-19 pandemic indicate that self-compassion plays a critical protective role in the mental health of different populations [32,33]. For instance, Gutiérrez-Hernández et al (2021) [34] observed that self-compassion was associated with lower emotional problems during the COVID-19 lockdown in Spain.…”
Section: Introductionmentioning
confidence: 99%